Isolation and Identification of S. aureus in Urinary Tract Infection - Eman Muftah Elzouki; Salwa Muftah Eljamay; Salma Awad Elzouki (Indonesian Journal of Community Services, 2023)
Urinary Tract Infection (UTI) defines a condition in which the urinary tract is infected with a pathogen causing inflammation which is a common, distressing, and occasionally life-threatening condition. Staphylococcus aureus is frequently isolated from urine samples obtained from long-term care patients. The significance of staphylococcal bacteriuria is uncertain. We hypothesized that S. aureus is a urinary pathogen and that colonized urine could be a source of future staphylococcal infection. Methods: This study focused on the frequency of S. aureus and its antibiotic susceptibility in different gender in the Derna District. A total of 200 UTI cases were reviewed in this study from Augustus 2022 to October 2022. Midstream specimens of urine, preferably of the first-morning void were collected from known UTI patients. Cultural and biochemical characterization of S. aureus Results: During this study period 200 samples were received, and from these samples, 170 bacterial isolates were obtained. Out of 170 isolates 160 were identified as S.aureus. Out of this predominant numbers were that of S.aureus 160 (94%), followed by other bacterial isolated 10 (6%). Also, it is shown that the highest number of S. aureus isolated were from married females (57.3%) followed by a male (42.7%). And it is showing 69.3% sensitivity toward Ciprofloxacin. Followed by Teicoplanin which shows 25.3% sensitivity, piperacillin, and Ofloxacin showed the lowest sensitivity. Thus our study showed that there were statistically significant differences between the isolated S.  aureus and age, gender, and marital status. We concluded that ciprofloxacin is a better antibiotic used for S. aureus.